Pengaruh Gaya Kepemimpinan, Keterlibatan Karyawan dan Kepuasan Kerja terhadap Komitmen Organisasi Dalam Meningkatkan Kinerja Karyawan pada Perusahaan Startup PT Perintis Teknologi Internasional di Malang - Budi Prabowo; Hani Dwi Arfinasari (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to examine and analyze the effect of leadership style, employee engafement and job satisfaction on organizational commitment in improving employee performance. The population used in this study were the thirty workers of PT Perintis Teknologi Internasional. This type of research is using a descriptive or survey research methodology, namely the presentation of quantitative data derived from field observations.This study used a closed questionnaire in the form of a Likert scale. Structural Equation Modeling (SEM) performs data processing using PLS (Partial Least Square). The results of this study indicate that leadership style has an effect on organizational commitment, employee engagement has an effect on organizational commitment, job satisfaction has an effect on organizational commitment, leadership style has no effect on employee performance, employee engagement has an effect on employee performance, satisfaction Work affects employee performance and organizational commitment affects employee performance. Keywords: Leadership style, employee engagement, job satisfaction, organizational commitment, employee performance